Influence of aluminum substitution on microstructural, electrical, dielectric and electromagnetic properties of sol-gel synthesized yttrium iron garnet (YlG) - Musa, Makiyyu Abdullahi; Azis, Raba’ah Syahidah; Dong, Xiangting; Osman, Nurul Huda; Hassan, Jumiah; Muhammad, Farah Diana; Mokhtar, Nurhidayaty (American Institute of Physics, 2020)
Aluminum-substituted Yttrium iron garnet, Al-YIG (Y3AlxFe5-xO12; x = 0.4, 0.8, 1.2, 1.6 and 2.0) samples were synthesized via auto combustion sol-gel technique. The obtained powder was heated at 950 °C, pressed into pellets and sintered at 1200 oC. The samples microstructures were studied using Field emissions scanning electron microscopy (FESEM). The average grain size decreased from 0.46 µm at x = 0.4 to a minimum value of 0.33 µm at x = 2.0. Elemental composition of the samples was studied by energy dispersive x-ray (EDX), while bulk density was measured by Archimedes principle. Electrical and dielectric measurements were carried out using Agilent impedance analyzer. Generally, the samples resistivity decreased with Al concentration. At 1 MHz frequency, the sample x = 0.4 has the highest resistivity of 2.19 × 105 Ωm which decreases down to its minimum value of 1.75 × 104 Ωm at x = 2.0. The dielectric constant for all the samples decreased with frequency. For the sample x = 0.4, the ε'r decreased from 49.03 at 40 Hz to 8.08 at 1 MHz. The dielectric loss tangent, tan δ decreased with increasing frequency, while it increased with Al substitution. Permeability values were calculated from permittivity data. The real ermeability decreases from 1263.12 at x = 0.4 to 6.96 at x = 1.2, and the decreased down to 11.74 at x = 2.0. The high dielectric constant, low resistivity and low loss values of the samples indicate their suitability for miniaturization of radio frequency devices, antenna and filter resonator.